Comparison study of the transradial prosthetics and biological hand using motion analysis approach - Abd Razak, N.A.; Abu Osman, Noor Azuan; Wan Abas, Wan Abu Bakar; Ahmad Fu'ad, A.N. (2011)
This paper presents the comparison study of the motion analysis between the transradial prosthetics and the biological hand that focuses on the supination/pronation and flexion/extension movements. The design of the new transradial prosthetics is based on combining the new approach on both body-powered prosthetics and electric-powered prosthetics. Two servo motors were used to generate the transradial motion while the shoulder ultrasonic sensor functioned as the input for the biomechatronics system. This paper briefly describes the kinetics and kinematics data of motion analyses that focus on the degree of maximum and minimum rotation of each motion. The data analysis of the transradial prosthetics is compared with the biological hand motion.